USING A MULTICULTURAL APPROACH IN THE SCHOOL CURRICULUM TO INCREASE SOCIAL AWARENESS AND INTERCULTURAL TOLERANCE - Dedi Gunawan Saputra (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine in depth how a multicultural approach in the school curriculum contributes to increasing students' social awareness and intercultural tolerance. The method used is a literature review by analyzing various scientific sources such as journal articles, books, theses and relevant educational policy documents. The results of the study show that the integration of multicultural values in curriculum design, learning practices, and the active role of teachers can encourage a broader understanding of cultural diversity, strengthen social empathy, and form tolerant attitudes in the school environment. Strategies such as the use of cultural narratives, interreligious dialogue, and contextual learning have proven effective in cultivating students' social sensitivity. However, challenges such as lack of teacher training, limited inclusive teaching materials, and resistance from the external environment are obstacles in implementing multicultural education as a whole. Thus, multicultural education has a strategic role in building a more inclusive and harmonious society, and needs to be systematically integrated into educational policies and practices at all levels.